Warm Footbaths with Sinapis nigra or Zingiber officinale Enhance Self-Reported Vitality in Healthy Adults More than Footbaths with Warm Water Only: A Randomized, Controlled Trial. (13th July 2021) - Vagedes, Jan; Kuderer, Silja; Helmert, Eduard; Kohl, Matthias; Beissner, Florian; Szöke, Henrik; Joos, Stefanie; Wolf, Ursula
Abstract : Objectives . To examine the effects of warm footbaths with thermogenic medicinal powders on vitality and heart rate variability in healthy adults. Intervention and Outcome . Seventeen healthy young adults (22.1 ± 2.4 years, 11 females) received three footbaths (WA: warm water only; GI: warm water and ginger; MU: warm water and mustard) in randomized order with a crossover design. We assessed vitality with the Basler Befindlichkeit questionnaire (BBS) and heart rate variability (HRV) before ( t 0), immediately after ( t 1), and 10 minutes following footbaths ( t 2). The primary outcome measure was self-reported vitality, measured via the BBS, at t 1. Results . The primary outcome measure, self-reported vitality, was higher after GI and tended to be higher after MU compared to WA with medium effect sizes (GI vs. WA, mean difference −2.47 (95% CI −5.28 to 0.34), p adj = 0.048, d adj  = 0.74), MU vs. WA, −2.35 (−5.32 to 0.61), p adj = 0.30, d adj  = 0.50). At t 2, the standard deviation of beat-to-beat intervals (SDNN) of HRV increased, and the stress index tended to decrease after all three footbath conditions with small to medium effect sizes (0.42–0.66). Conclusion . There is preliminary evidence that footbaths with thermogenic agents GI and MU may increase self-reported vitality during a short-time period with a more pronounced effect with GI. After a short follow-up, all three conditions tended to shift the autonomic balance towards relaxation. Future research should investigate these effects in clinical samples with a larger, more diverse sample size.